Analisa Kepribadian dan Kehidupan Sosial Remaja dengan Orang Tua dan Teman Pergaulan bagi Penyalahguna Napza di Lembaga Pemasyarakatan Kelas II B Kabupaten Rokan Hulu - Arbiah Marpaung; Zulfan Saam; yuyun Priwahyuni; Novita Rany; Irwan Muryanto (STIKes Hang Tuah Pekanbaru, 2021)
There are many factors that can cause adolescents to experience drug use, including the influence of association, the environment in which they live, joining in with friends, broken home families which are influenced by the lack of attention and communication between parents and children, as well as the pressure experienced during adolescence so they are prone to drug abused. From a field survey conducted by researchers in March 2020 at Penitentiary Rokan Hulu District, in 2018 there were 4 adolescents who were involved in drug problems, while in 2019 there were 18 teenagers (aged 13-19 years) who were detained in Penitentiary The purpose of this study is to analyze the personality and social life of adolescents with their parents and friends for drug abusers in Class II B Penitentiary, Rokan Hulu Regency in 2020. The research method used is qualitative with a phenomenological approach by conducting in-depth interviews with 13 informants about personality analysis and adolescent social life. The research informants consisted of 4 main informants of adolescent drug abusers in prison, and 9 supporting informants. The data analysis in this study was conducted qualitatively. The analysis was carried out by systematically arranging the interview guidelines and then the data was processed and presented the data descriptively. The implementation time of this study was started from April 1, 2020 to July 31, 2020. The results showed that most adolescents who abuse drugs have negative personalities, namely strength weak ego, most of the social relationships between adolescents and their parents are poor and less harmonious, mostly social relations between adolescents and their peers are unhealthy associations. Parents was a role model to their adolescents life, a harmonious family will have a good effect on adolescent interactions.